(untitled) - Phalen, Kathleen F. (Boston, 1998)
Presenting an investigative look at integrative medicine - a blend of Western and Eastern medicine, this text aims to help readers understand the history of, and the problems and promises inherent in both practices.
Keywords: Liều thuốc thay thế,Alternative medicine